Visual Hiperbole in Advertising (Reconnaissance) - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2023)
Extravagant exaggeration seems to be one of the most significant traits of contemporary culture influenced by the idea of success and ‘spectaclicity’. According to the Author of the paper, even the most extreme examples of hyperbole occur in advertising. The article presents several kinds of visual hyperbole which are used in contemporary adverts (these are: giga-hyperbole, multi-hyperbole, context hyperbole – situational and intertextual). The following examples of hyperbole have been described with respect to their distinctive features, main functions and imaginative value